CYP2C19 Phenotype, P2Y12 Inhibitor Selection, and Clinical Outcomes in Patients on Maintenance Clopidogrel Therapy - Rajiv C. Patel; Cameron D. Thomas; Joseph S. Rossi; Francesco Franchi; Ellen C. Keeley; Amber L. Beitelshees; Julio D. Duarte; Luis Ortega‐Paz; Natasha Kulick; Marshall Winget; Anh B. Nguyen; William E. Yang; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2025)
Background Use of CYP2C19 genotyping to guide antiplatelet therapy is associated with improved clinical outcomes in patients naïve to P2Y12 inhibitors undergoing percutaneous coronary intervention. The relationship between CYP2C19 genotype and clinical outcomes in patients on maintenance clopidogrel at the time of percutaneous coronary intervention is unknown. Methods This was a retrospective, multicenter cohort study. Patients were characterized as intermediate or poor metabolizers versus normal or rapid or ultrarapid metabolizers on the basis of CYP2C19 genotype. Major adverse cardiovascular events included cardiovascular death, myocardial infarction, ischemic stroke, or stent thrombosis. Results The study population (N=4246) had a median age of 63.0 (interquartile range, 55.0–71.0) years, was 66.8% men, and 21.3% Black individuals. During 12‐month follow‐up, major adverse cardiovascular event rates were higher (7.4% versus 4.8%; P<0.001) in the maintenance clopidogrel cohort (n=879) compared with the P2Y12 inhibitor naïve cohort (n=3367). In weighted Cox regression models of the maintenance clopidogrel cohort, major adverse cardiovascular event risk did not significantly differ in the clopidogrel‐treated intermediate/poor metabolizer group versus clopidogrel‐treated normal/rapid/UM metabolizer group (hazard ratio [HR], 0.88 [95% CI, 0.41–1.86]) versus the prasugrel‐ or ticagrelor‐treated group (HR, 0.73 [95% CI, 0.28–1.87]), although the confidence intervals were wide. In contrast, weighted major adverse cardiovascular events risk in the P2Y12 inhibitor naïve cohort was higher in the clopidogrel‐treated intermediate or poor metabolizers group compared with clopidogrel‐treated normal/rapid/ultrarapid metabolizer group or prasugrel‐ or ticagrelor‐treated group. Conclusions Patients on maintenance clopidogrel at the time of percutaneous coronary intervention represent a higher‐risk patient population than patients who are naïve to P2Y12 inhibitors and genotype‐guided P2Y12 inhibitor selection at the time of percutaneous coronary intervention may not provide clinical benefit.